2018
DOI: 10.1101/453530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of new therapeutic targets for osteoarthritis through genome-wide analyses of UK Biobank

Abstract: Osteoarthritis is the most common musculoskeletal disease and the leading cause of disability globally. Here, we perform the largest genome-wide association study for osteoarthritis to date (77,052 cases and 378,169 controls), analysing 4 phenotypes: knee osteoarthritis, hip osteoarthritis, knee and/or hip osteoarthritis, and any osteoarthritis. We discover 64 signals, 52 of them novel, more than doubling the number of established disease loci. Six signals fine map to a single variant. We identify putative eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…Further mechanistic data generated in model systems showed that SOST acts negatively on the WNT signaling pathway and led to the development of a novel antibody treatment Romosozumab (approved in 2018 for clinical use), which blocks SOST activity (1113). With the advent of genome-wide association studies (GWAS), and efficient whole-genome/exome sequencing (WGS/WES) data mapping there has been a sizeable increase in availability of human genetic data from cohort studies for musculoskeletal conditions including OP, high bone mass (HBM), and osteoarthritis (OA) (1420). Recent large cohort studies, such as UK-Biobank, have identified many new loci that contain novel osteogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Further mechanistic data generated in model systems showed that SOST acts negatively on the WNT signaling pathway and led to the development of a novel antibody treatment Romosozumab (approved in 2018 for clinical use), which blocks SOST activity (1113). With the advent of genome-wide association studies (GWAS), and efficient whole-genome/exome sequencing (WGS/WES) data mapping there has been a sizeable increase in availability of human genetic data from cohort studies for musculoskeletal conditions including OP, high bone mass (HBM), and osteoarthritis (OA) (1420). Recent large cohort studies, such as UK-Biobank, have identified many new loci that contain novel osteogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have revealed the polygenic nature of OA and to date over 90 independent risk loci have been identified 3e6 . The largest and most recent OA GWAS was carried out using the full UK Biobank cohort, with a focus on hip and knee OA 6 . This study utilised the genotypes of up to 455,000 individuals across 17.5 million single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…In this current study, we focussed on the OA signals that emerged from the analysis of the full UK Biobank cohort 6 and searched our cartilage genetic and epigenetic datasets to identify novel OA mQTLs. We were able to investigate a total of 42 signals and found evidence of mQTLs at ten of these.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the large-scale UK biobank identi ed genetic polymorphisms in eight genes associated with OA [10]. Three of these genes were linked to a cartilage formation/repair endotype, namely Growth Differentiation Factor 5 (GDF5), Fibroblast Growth Factor 18 (FGF18), and Transforming Growth Factorbeta 1 (TGF-β1) [10], suggesting that cartilage formation, when impaired, may be associated with a higher level of OA structural disease progression due to repair attenuation. Thus, cartilage formation by chondrocytes may represent a convergent mechanism with cartilage repair pathways.…”
Section: Introductionmentioning
confidence: 99%